Motivasi Belajar Seni Budaya Siswa SMP Negeri 1 Tanjung di Masa Pandemi Covid-19 - Ni Ketut Suparmi (Indonesian Publication Center, 2021)
Learning motivation is one of the characteristics possessed by students that are internal to themselves. Learning motivation can be influenced by the conditions of the learning being carried out. This qualitative descriptive study aims to determine how much student motivation in arts and culture subjects during the pandemic. This research was conducted at SMP Negeri 1 Tanjung, North Lombok with 15 students as respondents. The sample used is a saturated sample. Retrieval of research data using an instrument in the form of a questionnaire that has been adjusted to the indicator of learning motivation with the number of statements as many as 30 items. The data from this study were analyzed using a likert scale to determine the level of student motivation according to the table category. The results showed that the learning motivation of the students of SMP Negeri 1 Tanjung Lombok Utara was in the medium and high categories. From these results, it can be concluded that the learning motivation of students of SMP Negeri 1 Tanjung North Lombok is not low even though in online learning conditions the effects of the covid-19 pandemic are not unusual than what has been done.